Occupation-specific wage returns : shedding light on differentials between employees with a VET degree either with or without an Abitur - Friedrich, Anett [Verfasser]; Hirtz, Sandra [Verfasser] (My University, 2021)
"This study seeks to reveal the heterogeneity in occupation-specific wage returns among graduates of the German vocational education and training (VET) system. We distinguish between VET graduates with and without a higher education entrance certificate (i.e. an Abitur). To implement our hierarchical multi-level analyses, we exploit the latest wave of the BIBB/BAuA Employment Survey from 2018. By estimating occupation-specific wage returns, we reveal gaps between VET graduates with and without an Abitur. Additionally, we analyse several occupational characteristics to show how they contribute to the gaps in wage returns between our study groups. Our results show that employees combining an Abitur with a VET degree achieve higher wage returns than those VET graduates without an Abitur across all occupations. Employees holding a VET degree without an Abitur display greater inequality of occupation-specific wage returns. Among the occupational characteristics, task composition is the main driver of the differences in wage returns." (Authors' abstract, BIBB-Doku)
Keywords: G 1.3.3.1 Qualifikationsverwertung; G 1.3.2.1.2 Hochschulzugangsberechtigung; T 3.5 Statistik; 370; Bildungsökonomie; Schulabschluss; Abitur; Bildungsertrag; Einkommen; Vergleichsuntersuchung; Mehrebenenanalyse; BIBB-/BAuA-Erhebung; Quantitative Angaben